FROM IDEALISM TO DISILLUSIONMENT: THE TENOR’S VOCAL EXPRESSION IN SHI GUANGNAN’S REGRET FOR THE PAST - Wen , Sihui; Tee , Xiao Xi (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
This paper discusses the transformation of poetic tenor heroism in an opera by Shi Guangnan titled Regret for the Past, paying specific attention to the use of voice and interpretation technique. It examines the interaction between tenor technique (the expressive control of Tessitura, legato phrasing, dynamic nuance, and tone colour) and musical structure in the portrayal of a heroic image in a particular cultural context. Based on the analysis of the score and the practice of performance, the paper identifies idiomatic elements of Shi's composition that allow vocalists to convey the heroic determination and its gradual decadence and, thus, combine music and narrative into one expressive curve. Tracing the emotional trajectory of Juan Sheng throughout the seasonality of the opera: the sunny exuberance of youthful attraction, the philosophical depression of loss, and, lastly, the downfall of tragedy. The paper claims that the work is an inimitable lyrical subjectivity in combination with social criticism in the context of the post-socialist Chinese opera aesthetics and evolving concepts of heroism. Finally, heroism in opera is redefined to emphasise perseverance and poetic greatness, where moral self-criticism is more important than success within the boundaries of history.